Decreasing Supermarket Tantrums by Increasing Shopping Tasks: Advantages of Pre-Teaching. (January 2014) - Greenwald, Ashley E.; Williams, W. Larry; Seniuk, Holly A.
A brief training package consisting of pre-teaching of appropriate grocery item–gathering skills and reinforcement for appropriate behavior was used to teach a child diagnosed with autism to remain in a store and participate in shopping without exhibiting tantrums. The training package began with teaching the necessary component skills and expectations in the participant's home, and these skills were then established at a local supermarket.